A Case of Bacteremia and Meningitis Associated with Piperacillin-Tazobactam Nonsusceptible, Ceftriaxone Susceptible Escherichia coli during Strongyloides Hyperinfection in an Immunocompromised Host - Santosh Dahal; Jeffrey Lederman; Jesse Berman; Marius Viseroi; Stephen Jesmajian (Case Reports in Infectious Diseases)
Strongyloidiasis is an emerging parasitic infection with intriguing epidemiology, presentation, and clinical management. We report a case of hyperinfection syndrome complicated by E. coli bacteremia and meningitis with one of the isolates showing a unique resistance pattern recently being recognized. This report describes the aspect of invasive bacterial infections in strongyloidiasis and highlights the unique susceptibility pattern of the E. coli isolate and the extreme caution required during the antibiotic therapy.